Effect of Rumensin on legume bloat in cattle - M.P. Katz; E.E. Bartley; E.S. Pressman; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1982)
Rumensin with or without Bloatguard was fed to rumen-fistulated cattle grazing lush alfalfa pasture. Although Rumensin alone or in combination with low doses of Bloatguard reduced bloat, it was not completely effective. Hence, Bloatguard at the recommended dose is still necessary for full bloat control.
Keywords: Cattlemen' s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Rumensin; Legume bloat; Alfalfa